2018
DOI: 10.1111/aos.13968
|View full text |Cite
|
Sign up to set email alerts
|

IgG4‐related disease in patients with idiopathic orbital inflammation syndrome: data from the French SIOI prospective cohort

Abstract: Purpose To better characterize IgG4‐related disease (RD) in the setting of idiopathic orbital inflammation syndrome (IOIS). Methods National, multicentre, prospective, observational cohort study. Among the patients consecutively included in the French multicentre SIOI cohort, we selected those who underwent orbital and/or adnexal biopsy. Clinical, morphological and pathological findings at diagnosis were blindly analysed. Serum IgG4 levels at inclusion were measured and all available biopsy specimens were immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
5
12
0
1
Order By: Relevance
“…We observed that bilateral ocular adnexal disease and an enlargement of the infraorbital nerve were more frequent in IgG4-RD than in non-IgG4-RD patients. In agreement with previous studies, IgG4-RD showed similarities with several of the clinical characteristics of IOI, which, in general, tends to affect men more than women [3,14,17]. Our study revealed that non-IgG4-RD patients were mostly female, which is similar to the findings in published studies [1,18].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We observed that bilateral ocular adnexal disease and an enlargement of the infraorbital nerve were more frequent in IgG4-RD than in non-IgG4-RD patients. In agreement with previous studies, IgG4-RD showed similarities with several of the clinical characteristics of IOI, which, in general, tends to affect men more than women [3,14,17]. Our study revealed that non-IgG4-RD patients were mostly female, which is similar to the findings in published studies [1,18].…”
Section: Discussionsupporting
confidence: 92%
“…Data were reviewed, including age, sex, affected eye, visual acuity (VA), signs and symptoms, the location and extent of the disease, radiologic data, histopathologic features, and treatment outcome. Blood eosinophilia was defined as a percentage of eosinophils > 10 [14].…”
Section: Data Collectionmentioning
confidence: 99%
“…Tiegs-Heiden et al reported that among the patients with IgG4-ROD in their study, sinusitis was present in 89% [10]. Eosinophilia associated with recurrent sinusitis or asthma has been found to be a prominent feature in patients with definite IgG4-RD [11]. The inflammatory mucosal thickening noted in the paranasal sinuses has an unknown association with IgG4-ROD, with a potential link between IgG4 positivity and Th2 immune response being one possibility presented [11].…”
Section: Discussionmentioning
confidence: 90%
“…Eosinophilia associated with recurrent sinusitis or asthma has been found to be a prominent feature in patients with definite IgG4-RD [11]. The inflammatory mucosal thickening noted in the paranasal sinuses has an unknown association with IgG4-ROD, with a potential link between IgG4 positivity and Th2 immune response being one possibility presented [11]. The presence of sinusitis may offer an additional clue when the diagnosis of IgG4-RD is considered.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similar to our study, other studies have found that the serum level of IgG4 is often but not always elevated in patients with IgG4-RD, 26 approximately only two-thirds of patients with IgG4-RD have elevated serum IgG4 levels, 27 and only 23% of pathologically identified patients with IgG4-positive IgG4-RD had elevated serum IgG4 levels. 28 The relative dys-synchrony of serum and pathologic IgG4 may provide two possible explanations for the overabundance of IgG4 antibodies: tissue-destructive immunoglobulins and the response to an unknown primary inflammatory stimulus. 1 However, we found that patients with either histopathological or serum IgG4 positivity still presented a series of unique clinicopathologic features compared with IgG4-negative patients with TED, indicating a more active and severe subtype.…”
Section: Discussionmentioning
confidence: 99%